2002
DOI: 10.1540/jsmr.38.87
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide(NO) Primarily Accounts for Endothelium-Dependent Component of .BETA.-Adrenoceptor-Activated Smooth Muscle Relaxation of Mouse Aorta in Response to Isoprenaline.

Abstract: Isoprenaline is known to produce vascular relaxation through activation of β-adrenoceptors. In recent years, β-adrenoceptor-activated vascular relaxation has been the focus of pharmacological study in terms of both the receptor subtypes and the intracellular signaling mechanisms which trigger smooth muscle mechanical functions. In addition, the possible contribution of the endothelium to β-adrenoceptor-activated relaxation of vascular beds has provoked considerable discussion, with consensus still to be establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
0
22
0
3
Order By: Relevance
“…Nevertheless, there is also evidence for and against the endothelium dependence of this response due to the variability between the species and the vascular bed; inconsistency was also found even in the same vessel. Thus, Adrb-mediated relaxation has been described as being completely or partially endothelium-dependent in aorta from rat (Gray and Marshall, 1992;Brawley et al, 2000a;Ferro et al, 2004) and mouse (Akimoto et al, 2002), and as being totally endothelium-independent in rat aorta (Moncada et al, 1991;Eckly et al, 1994;Satake et al, 1996). Conflicting results have also been reported in rat MRA, where we found that Adrbmediated vasodilatation was independent of endothelial NO (Briones et al, 2005), while other authors showed NO-dependent relaxation (Graves and Poston, 1993).…”
Section: Introductionmentioning
confidence: 53%
“…Nevertheless, there is also evidence for and against the endothelium dependence of this response due to the variability between the species and the vascular bed; inconsistency was also found even in the same vessel. Thus, Adrb-mediated relaxation has been described as being completely or partially endothelium-dependent in aorta from rat (Gray and Marshall, 1992;Brawley et al, 2000a;Ferro et al, 2004) and mouse (Akimoto et al, 2002), and as being totally endothelium-independent in rat aorta (Moncada et al, 1991;Eckly et al, 1994;Satake et al, 1996). Conflicting results have also been reported in rat MRA, where we found that Adrbmediated vasodilatation was independent of endothelial NO (Briones et al, 2005), while other authors showed NO-dependent relaxation (Graves and Poston, 1993).…”
Section: Introductionmentioning
confidence: 53%
“…In this sense, acute pharmacological stimulation of β-AR induces full relaxation if the endothelial cells are intact in rat aorta [4,5] and resistance arteries [6,7,8], in mouse conductance and resistance vessels [9,10] and in human vasculature [11]. However, these results contrast with other data obtained from different species and vessel types that showed no role of the endothelium in acute relaxation mediated by β-AR agonists [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mouse is recently used increasingly for vascular investigation because a wide variety of gene deletion and overexpression are available in this rodent species. Accordingly, fundamental characteristics regarding vascular contraction and relaxation of normal (wild) mouse are being revealed (Akimoto et al, 2002;Ashton et al, 2000;Chan and Fiscus, 2001;Chruscinski et al, 2001;Hosoda et al, 2005;Pomerleau et al, 1997;Russell and Watts, 2000;Shibano et al, 2002;Koike, 2001a, 2001b). Distribution of α1-adrenoceptor (α1-AR) subtypes is one of such issues that are being focused.…”
Section: Introductionmentioning
confidence: 99%